Integration of logistics and cloud computing service providers: cost and green benefits in the Chinese context - Subramanian, Nachiappan; Abdulrahman, Muhammad D.; Zhou, Xiaolai (Elsevier, 2014)
Drawing on the innovation diffusion theory and data from 236 Chinese small and medium-sized logistics service providers (SMLSPs), this study developed and tested a conceptual model for empirically examining the green and cost benefits of integration between cloud service providers and SMLSPs in the Chinese context. The study posits that the perceived green and cost benefits drive the need for cloud computing (CC) adoption by Chinese SMLSPs. The results indicate that Chinese SMLSPs are attracted by CC to reduce cost in a short term and to gain sustainability through green benefits in a long term. The study extends CC capabilities and enterprise integration literature in the context of logistics services.